SAR measurement of ocean sea surface wind and wave for operational ship routing - Li, Xiao Ming; Lehner, Susanne; Bruns, Thomas (International Geoscience and Remote Sensing Symposium (IGARSS), 2011)
Safety of shipping is a growing concern. The causes of shipping casualties are various, while over 30% of the casualties are due to bad weather. Heavy sea state and severe weather conditions have caused the loss of more than 200 large cargo vessels within 20 years between 1981 and 2000. © 2011 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: SAR; shipping security; wind and wave measurement